2014
DOI: 10.1007/s12540-014-5016-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the dehydrogenation speed and Nd content on the microstructure and magnetic properties of HDDR processed Nd-Fe-B magnets

Abstract: The effect of Nd content and dehydrogenation speed on the microstructure and magnetic properties of hydrogenation-disproportionation-desorption-recombination (HDDR) processed Nd-Fe-B magnetic powders was studied. The NdxB6.4Ga0.3Nb0.2Febal (x=12.5-13.5, at.%) mold casting alloys were subjected to HDDR process after homogenization heat treatment. During desorption-recombination stage, dehydrogenation speed and time were systematically changed to control the speed of the desorption-recombination reaction. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…It should be however noted that the remanence of 820 • C-DR treated HDDR powders is higher than that of 810 • C-DR treated HDDR powders in the Nd content range from 12.5 to 13.5 at.%. This result is consistent to our previous result in which slow DR speed suppressed temperature drop during DR stage and resultingly enhanced remanence due to highly textured microstructure [11]. Based upon these results, it can be concluded that higher temperature during DR stage results in higher degree of anisotropy of the HDDR powders.…”
Section: Methodssupporting
confidence: 92%
“…It should be however noted that the remanence of 820 • C-DR treated HDDR powders is higher than that of 810 • C-DR treated HDDR powders in the Nd content range from 12.5 to 13.5 at.%. This result is consistent to our previous result in which slow DR speed suppressed temperature drop during DR stage and resultingly enhanced remanence due to highly textured microstructure [11]. Based upon these results, it can be concluded that higher temperature during DR stage results in higher degree of anisotropy of the HDDR powders.…”
Section: Methodssupporting
confidence: 92%